ANALISIS PRODUKSI DAN MARJIN PEMASARAN USAHATANI KUBIS DI DESA AIR DUKU KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Fitria, Indah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Indonesia is an agricultural country, meaning that agriculture plays an important role throughout the nation. This can be shown from the large number of residents or workers who live or work in the agricultural sector or agricultural products that come from agriculture (Pulungan, 2008). Most people in Indonesia depend on the agricultural sector for their livelihoods. Farming communities who work in the agricultural sector mostly live in rural areas. In general, Indonesian residents who live in rural areas have relatively low levels of income when compared to residents who live in urban areas. The difference in revenue is closely related to the productivity of Indonesian farmers which cannot be separated from various factors, including the area of land owned and government policies in terms of providing incentives to farmers and so on. Efforts that can be made to increase the productivity of cabbage plants are by increasing the prices received by farmers. The high and low prices of cabbage experienced by farmers make it necessary for us to know what price levels are obtained by traders, this is because there are price differences between producer farmers and traders. The price level at marketing institutions will influence the price level at producer farmers, by knowing the marketing margin obtained from the marketing of cabbage. With the above situation, farmers as producers, apart from increasing their production, also need a marketing institution that provides certainty of marketing their production at a reasonable price. Marketing channels involve marketing institutions which are intermediary institutions between producers and consumers. Based on these conditions, it is hoped that good cooperation will occur between intermediary institutions and producer farmers. From the description above, this research aims to analyze the production and marketing margins of cabbage farming in Air Duku Village, Selupu Rejang District, Rejang Lebong Regency.